Diversity of marine fungi associated with wood baits in the estuary Ria de Aveiro, with descriptions of Paralulworthia halima, comb. nov., Remispora submersa, sp. nov., and Zalerion pseudomaritima, sp. nov. (4th May 2021) - Gonçalves, Micael F. M.; Abreu, Alberto C.; Hilário, Sandra; Alves, Artur
ABSTRACT: Lignicolous marine fungi are a particular group of microorganisms that are typically found in mangroves, salt marshes, and estuaries, normally associated with driftwood or submerged wood. During investigations of lignicolous fungi occurring in the estuary Ria de Aveiro, Portugal, wood baits were submerged in a marina for 1 year. Seventeen distinct marine fungal species were identified, with the most abundant taxa belonging to the family Lulworthiaceae. Through single- and multilocus phylogenies based on sequences of the internal transcribed spacer (ITS) region and large subunit (28S) and small subunit (18S) of the ribosomal RNA gene cluster in combination with morphological and physiological data, we describe Remispora submersa, sp. nov., and Zalerion pseudomaritima, sp. nov., as novel species. Additionally, we propose that Papulaspora halima, a species whose taxonomic placement has been somehow confusing, be transferred to the genus Paralulworthia as Paralulworthia halima .